Development of Accounting Concepts to Overcome the Economic Crisis: A Case Study of the Indonesian Tourism Industry During the COVID-19 Pandemic - Judijanto, Loso; Puspitasari, Nindy; Suryaningrum, Dyah Ayu (Westscience Press, 2024)
The global economy is facing previously unheard-of difficulties as a result of the COVID-19 epidemic, with the tourism sector being particularly hard hit. This qualitative study looks into how the pandemic's effects on the country's tourism industry have caused adaptive adjustments in accounting procedures. The study examines four major themes: the immediate economic impact on the sector, adaptive modifications in accounting methods, implementation obstacles, and the efficacy of these adaptive concepts. Thematic analysis and NVivo are utilized to gather in-depth interviews with fifteen stakeholders. The results show a landscape of financial transformation characterized by agile budgeting, scenario-based modeling, real-time reporting, and technological integration. Notwithstanding the achievements, problems including resource limitations and change aversion are noted. The research offers significant perspectives for companies, decision-makers, and scholars that aim to comprehend and manage difficulties in the travel and tourism sector.